GROWTH IN NURSERY AND GROW-OUT PHASES OF WHITE SHRIMP AFTER IMMERSED IN RECOMBINANT GIANT GROUPER GROWTH HORMONE - Aulia Saputra; Odang Carman; . Alimuddin (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
The growth of white shrimp (Litopenaeus vannamei) can be improved by using recombinant fish growth hormone through immersion. This research was performed to evaluate the white shrimp growth at nursery and grow-out phases after recombinant giant grouper growth hormone (rElGH) immersion. Shrimp were immersed at different stages in one liter seawater containing 15 mg rElGH for two hours. At the nursery stage 30,000 PL4 that previously immersed at nauplius stage (treatment A1), at PL4 (treatment B1) and control without rElGH immersion (K1) were reared in fiber tanks containing 750 L seawater for 8 days. At the grow-out phase, 100 PL11 that have been immersed in rElGH solution at nauplius stage (treatment A2), at PL4 (B2), PL11 (C2) and control without rElGH immersion (K2) were separately reared in fiber tanks containing 750 L seawater for 55 days. Each treatment consisted of three replications. The results showed that at the end of the nursery phase, B1 treatment increased 19% of body length, 30.2% of the body weight and decreased the coefficient of length variation 34.9% compared to control K1 (P<0.05). At the grow-out phase, C2 treatment enhanced 38.2% of body weight and 32% of biomass compared with control K2 (P<0.05). Thus, hatchery is better to immerse PL4, and the farmer should used rElGH-immersed PL11 for growing-out.Keywords: growth promoting, nursery, grow out, Litopenaeus vannamei, rElGH